MANAJEMEN RAPAT OLEH PIMPINAN PONDOK PESANTREN MODERN NURUL HARAMAIN NWDI BOGOR - Maryani, Novi; Priyatno, Agus; Haris, Ridwan; Suhartini, Een; Hakim, Luqmanul (AKSI: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to provide an overview of the implementation of meeting management in Islamic boarding schools as well as the principles and theory of meeting management in offices. This research was conducted using a descriptive qualitative approach and data collection was obtained through interviews and collecting references via the internet. Meeting management is implemented by applying the principles of meeting implementation, namely planning, organizing, directing and controlling. In managing the meeting, the personnel involved are the leaders of the pesantren, namely kyia, ustadz and ustadzah, as well as senior santri. Meetings are held regularly once a week, which are called coordination meetings and work meetings which are held once a year since the start of the new school year. The leadership of the islamic boarding school has not been able to solve the problems that exist in the islamic boarding school environment. Islamic boarding school leaders should be able to establish coordination in solving existing problems so that they can achieve the goals that have been set.